Perceptions of, and attitudes towards, varieties of English in the Cape Peninsula, with particular reference to the Ê¾coloured communityÊ¾ - Wood, Tahir Muhammed (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 1988)
This study set out to analyse the concept of the Ê¾coloured communityÊ¾ and to describe the linguistic phenomena associated with it. It was found that the community was characterized by division and an overt rejection of 'coloured' identity. A satisfactory definition of the community could only be arrived at by exploring social psychological and anthropological concepts, particularly that of the social network, and a covert identification was postulated. This in turn was used to explain the linguistic phenomena which were found to be associated with the community. The latter included a vernacular dialect consisting of non-standard Afrikaans blended with English, as well as a stratification of particular items in the English spoken by community members . This stratification was analysed in terms of the social distribution of the items, enabling comparisons to be made with the English spoken by Ê¾whitesÊ¾. A fieldwork study was embarked on with the intention of discovering the nature of the perceptions of, and attitudes towards, the idiolects of certain speakers. These idiolects were considered to be typical and representative of the forms of English normally encountered in the Cape Peninsula, and were described in terms of the co-occurrences of linguistic items which they contained. Tape recordings of the speech of this group of speakers were presented in a series of controlled experiments to subjects from various class and community backgrounds who were required to respond by completing questionnaires. It was found that those lects which contained items and co-occurrences of items peculiar to 'coloured' speakers were associated with lower status than those containing items and co-occurrences of items peculiar to 'white' speakers. Attitudes towards speakers were found to be more complex and depended upon the styles and paralanguage behaviours of the speakers, as well as accent, and also the psychological dispositions of the subjects who participated
Keywords: English language -- South Africa -- Cape of Good Hope; English language -- Variation; Sociolinguistics -- South Africa